Sedoanalgesia Strategies and their Potential Benefits in the Intensive Care Unit: Narrative Review of the Literature - Arango-Martínez, Alejandro; Penagos-Sanchez, Sebastian; Restrepo-Arismendy, Simón; Arias-Correa, Ruber Hernando (Iatreia)
Introduction: Sedoanalgesia is one of the main strategies used in the intensive care unit (ICU), aimed at reducing the presentation of associated adverse effects. However, to date there is a lack of an adequate description of its new and potential benefits. Objectives: To critically review the available evidence on the selection of drugs used in sedoanalgesia and describe their potential pharmacological benefits in the critically ill patients. Methods: A review of the literature was conducted from 1990 to 2022, considering the corresponding MeSH terms for sedation, benzodiazepines, dexmedetomidine, intravenous anesthetics, and intensive care unit. The information was extracted and synthesized in a structured manner according to the recommendations of the SANRA guidelines. Results: Lower rates of delirium and ICU stay were found for dexmedetomidine, while for midazolam and propofol a possible anti-inflammatory effect was found, and for ketamine a potential benefit in the hemodynamic profile was suggested. Conclusions: Multiple beneficial effects of these drugs have been proposed, however, the evidence is scarce and studies with a better methodological design are needed to reach valid conclusions.